2015
DOI: 10.1016/j.jesp.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Collective punishment depends on collective responsibility and political organization of the target group

Abstract: • Collective responsibility increases support for collective punishment. • This effect is stronger for democratic groups, as compared to nondemocratic groups. • The value of democracy creates higher expectations for democratic groups. • Violated expectations decrease group value, increasing punishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 47 publications
1
24
1
Order By: Relevance
“…We rather suggest that the value of democracy infuses any justice judgment in relation with democratic and nondemocratic groups. In support for this argument, other studies have found that support for the punishment of the group leader closely followed the pattern of support for the collective punishment of the group (Pereira et al, ). In order to provide a clear answer to this question, future research should compare different justice judgments, such as support for the offender punishment and perceived wrongdoing legitimacy within the same experiment to test whether the same dynamics emerge.…”
Section: Discussionsupporting
confidence: 92%
“…We rather suggest that the value of democracy infuses any justice judgment in relation with democratic and nondemocratic groups. In support for this argument, other studies have found that support for the punishment of the group leader closely followed the pattern of support for the collective punishment of the group (Pereira et al, ). In order to provide a clear answer to this question, future research should compare different justice judgments, such as support for the offender punishment and perceived wrongdoing legitimacy within the same experiment to test whether the same dynamics emerge.…”
Section: Discussionsupporting
confidence: 92%
“…In spite of that, punishments often are inflicted upon people for a wrongdoing that they did not commit: Collective punishments entail situations in which an entire group is punished for a wrongdoing perpetrated only by a subset of its group members [ 9 ]. Support for such treatments has been shown to be shaped by the group’s political organization [ 9 ], collective responsibility [ 10 ], as well as by perceptions of value-violations from the offender group [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the above studies establish a link between group entitativity and direct retaliation, none of these previous studies has specifically focused on third-party collective punishment, i.e. the punishment of an entire group for the misdeed of a few group members by an external agent [ 9 , 10 ]. Indeed, goup punishment judgments examined in that earlier work were mostly second-party judgments, such as retaliatory collective punishments by the victim following a rejection [ 24 ] or a provocation [ 26 ], and vicarious punishments (or group-based retaliation)—i.e.…”
Section: Introductionmentioning
confidence: 99%
“…All the studies described in this paper have received approval from the Ethical Committee of the Psychology and Educational Sciences Faculty of University of Geneva 4. In these studies, we also assessed the perceived legitimacy of collective punishment (see Berent, et al, 2016aBerent, et al, , 2016bPereira, et al, 2015). As in past studies (Berent et al, 2016a(Berent et al, , 2016b and for reasons we still ignore, the pattern of findings for measures of perceived legitimacy were somewhat inconsistent across the studies presented here.…”
Section: Discussionmentioning
confidence: 79%